Preparation method of nickel-silver-tungsten composite electric contact material, electric contact material and electric contact

The nickel-silver-tungsten composite material was prepared by electroless plating and electrospark sintering technology was used to prepare the nickel-silver-tungsten composite material, which solved the problem of insufficient structural uniformity and conductivity of the silver-tungsten composite material, and achieved efficient arc erosion resistance and mechanical strength increase.

CN119282108AActive Publication Date: 2025-01-10ZHEJIANG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411180214.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2025-01-10
Estimated Expiration
2044-08-27

AI Technical Summary

Technical Problem

The existing silver-tungsten composite materials have defects in structural uniformity and conductivity, and the thermal sintering and metal seepage technology are complex and costly, making it difficult to ensure high conductivity.

Method used

The surface of the tungsten powder is coated with silver and nickel nanoparticles by electroless plating to form a silver-nickel bimetallic layer clad structure. After uniform mixing of solution ball milling, nickel-silver-tungsten composite material is prepared by electrospray plasma sintering technology.

Benefits of technology

It improves the compressive strength, ductility and arc corrosion resistance of the material, reduces internal micropores, improves structural uniformity and mechanical strength, and reduces preparation costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119282108A_ABST
    Figure CN119282108A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a nickel-silver-tungsten composite electric contact material, an electric contact material and an electric contact, silver and nickel metal nanoparticles are introduced to the surface of tungsten powder in a layered coating manner by adopting a chemical plating method to obtain tungsten powder with a core-shell structure tightly coated by a silver-nickel bimetal layer; then uniformly mixing tungsten powder and silver powder with different mass fractions and core-shell structures through a solution ball milling method; and finally, crystallizing and curing the mixed powder by adopting an electric spark plasma sintering technology to obtain a series of nickel-silver-tungsten composite electric contact materials. The nickel-silver-tungsten composite electric contact material provided by the invention has good compressive strength, excellent ductility and excellent arc erosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of low-voltage electric contact, and in particular relates to a preparation method of a nickel-silver-tungsten composite electric contact material, an electric contact material and an electric contact. Background Art

[0002] Electrical contact materials are widely used in electronic and electrical systems, such as power relays, electrical switches, circuit breakers, fixed electrical connectors, etc. They play a fundamental role in controlling the on and off of circuit current and carrying loads, and are essential to ensure the efficiency and reliability of electrical equipment and electronic products. As the heart of the electrical contact, these electrical contact materials must have high electrical conductivity and thermal conductivity, good arc erosion resistance, excellent processing performance and good mechanical properties. In order to meet the above various performance requirements, electrical contact materials are usually composite materials composed of a metal matrix (Ag or Cu) reinforced by one or more reinforcing materials, in which the metal provides electrical conductivity and thermal conductivity, and the reinforcing material provides strength, hardness, and arc erosion resistance. Compared with copper-based composite materials, which are mainly used in the field of high-voltage electrical contacts, silver-based composite electrical contact materials show higher electrical conductivity and thermal conductivity at the same metal mass fraction, benefiting from the inherent properties of metallic silver. Therefore, they have more advantages in medium and low voltage electrical applications, especially in emerging microelectronic devices and integrated circuits. So far, a large number of silver-based contact materials with ceramics (CdO, SnO2, CuO, Ti3SiC2, Ti3AlC2) and metals (W, Ni, Cu, Ti) as the main reinforcement materials have been developed. Although ceramics have the characteristics of high strength, high modulus and high melting point, they lack easily excited free electrons and effective dislocation movement, making the conductivity and toughness of the composite material unsatisfactory. Due to the presence of metallic bonds in metals, they usually have high conductivity and excellent fracture toughness. As one of them with excellent arc erosion resistance, metal tungsten plays an important role in enhancing the hardness, strength and service life of silver-based composite contact materials.

[0003] The mechanical properties and structural properties of silver-based composite electrical contact materials are mainly determined by the structural characteristics of the composite material and the uniformity of the reinforcement dispersion. In order to solve the shortcomings of W-Ag composite materials caused by the huge difference in physical properties and mutual incompatibility (such as the difficulty in ensuring structural uniformity and the arc erosion process will produce tungsten oxides with poor conductivity), people have proposed many improvement strategies. Here, the relevant technologies retrieved are mainly the following three: the first is structural modification, which improves the structure of the initial W powder through chemical reactions or related processes, such as the common core-shell structure, using the special structural characteristics of the powder to promote the structural uniformity of the sintered material; the second is component modification, which is mainly to introduce other elements into the composite system during the powder preparation process or during the sintering process. Common ones include metal single silver, copper, nickel and ceramic phase material tungsten carbide, etc., and use doping substances as lubricants or metal binders to enhance the indirect wettability of tungsten and silver phases and improve the overall comprehensive performance of the material; the third is to change the thermal processing technology of the material. The common thermal processing technologies used for silver-tungsten composite contact materials are hot pressing sintering and metal infiltration technology. In order to ensure the structural tightness of the silver-tungsten composite material, the hot pressing sintering technology usually requires a higher pressure and a processing temperature below the melting point of silver (960°C). The metal infiltration technology requires a step-by-step process, that is, first sintering the tungsten powder under high temperature and pressure into a tungsten skeleton, and then filling the liquid silver into the gaps of the tungsten skeleton through infiltration to obtain a bulk material.

[0004] Although the above three related technologies can improve the defects of poor two-phase wettability and uneven structure of silver-tungsten composite contact materials to a certain extent, the inventors found that the above related technologies have at least the following technical problems: (1) Structural and component modifications are conducive to improving the structural advantages of single-phase powder particles, but the uniformity of two-phase powder mixing needs to be further improved; (2) Hot pressing sintering technology often requires high temperature and high pressure for more than several hours, and the preparation process of metal infiltration technology is relatively complicated and the preparation cost is high. It is difficult to ensure that the electrical conductivity of the composite material is at a relatively high level.

[0005] Therefore, the development of new silver-based composite materials with excellent performance for the electrical field and the corresponding preparation process is of great significance to saving precious metal resources, improving the conductivity, strength and arc erosion resistance of contact materials, and improving the stability of product quality. Summary of the invention

[0006] The first object of the present invention is to provide a method for preparing a nickel-silver-tungsten composite electrical contact material, in the hope of at least partially solving the above-mentioned technical problems.

[0007] To this end, the above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0008] A method for preparing a nickel-silver-tungsten composite electrical contact material comprises the following steps:

[0009] S1. Chemical plating under mild conditions in an aqueous solution system:

[0010] A layer of silver nanoparticles is coated on the surface of the tungsten powder to obtain a tungsten powder coated with a single layer of metallic silver;

[0011] A layer of nickel nanoparticles is coated on the surface of the obtained single metal silver-coated tungsten powder to obtain a tungsten powder coated with a silver-nickel bimetallic layer;

[0012] S2, using solution ball milling, mixing the tungsten powder coated with the silver-nickel bimetallic layer with the silver powder using anhydrous ethanol as a dispersant to obtain a composite powder;

[0013] S3. Using spark plasma sintering, the composite powder is sintered and solidified under high temperature, high pressure and vacuum conditions to obtain a nickel-silver-tungsten composite electrical contact material.

[0014] While adopting the above technical solutions, the present invention may also adopt or combine the following technical solutions:

[0015] As a preferred technical solution of the present invention: before step S1, the tungsten powder is sensitized by using hydrochloric acid and stannous chloride dihydrate aqueous solution.

[0016] As a preferred technical solution of the present invention: in step S1, a layer of silver nanoparticles is plated on the surface of tungsten powder using silver nitrate as a silver source, ammonia water as a complexing agent, polyvinyl pyrrolidone as a dispersant, sodium hydroxide aqueous solution as a pH regulator, and glucose as a reducing agent to obtain a single-layer metallic silver-coated tungsten powder.

[0017] As a preferred technical solution of the present invention: the amount of silver nitrate is 0.85-1.7g, the amount of ammonia water is 2-4mL, the amount of polyvinyl pyrrolidone is 0.1-0.2g, the amount of glucose is 0.35-0.7g, the mass of tungsten powder is 2-10g, and the pH value of the solution is between 11-11.5;

[0018] The water bath temperature of the reaction was 40°C and the rotation speed of the magnetic stirrer was 500 rpm.

[0019] As a preferred technical solution of the present invention: in step S1, nickel sulfate hexahydrate is used as a nickel source, sodium pyrophosphate is used as a complexing agent, ammonia water is used as a pH regulator, and dimethylamine borane is used as a reducing agent, and a layer of nickel nanoparticles is plated on the surface of the tungsten powder coated with a single layer of metallic silver to obtain a tungsten powder coated with a silver-nickel bimetallic layer.

[0020] As a preferred technical solution of the present invention: the amount of nickel sulfate hexahydrate is 5-6g, the amount of sodium pyrophosphate is 10-12.5g, the amount of ammonia water is 8-10mL, the amount of dimethylamino borane is 0.3-0.4g, and the mass of the single-layer metal silver-coated tungsten powder is 10.5-21.0g;

[0021] The water bath temperature of the reaction was 25 °C, and the speed of magnetic stirring was 600 rpm;

[0022] As a preferred technical solution of the present invention: in step S1,

[0023] After the reaction is completed, the tungsten powder coated with a single layer of metallic silver needs to be filtered, washed with water and vacuum dried.

[0024] After the reaction is completed, the tungsten powder coated with the silver-nickel bimetallic layer needs to be filtered, washed with water and vacuum dried.

[0025] As a preferred technical solution of the present invention: in step S1, the vacuum drying temperature is 40° C. and the time is 8 hours.

[0026] As a preferred technical solution of the present invention: in step S2,

[0027] The ratio between the total mass of the tungsten powder and the silver powder coated with the silver-nickel bimetallic layer and the mass of the ball milling medium is 1:10;

[0028] The ratio between the total mass of the tungsten powder and the silver powder coated with the silver-nickel bimetallic layer and the mass of the anhydrous ethanol is 1:4;

[0029] The ball milling speed was 250 rpm and the time was 40 minutes.

[0030] As a preferred technical solution of the present invention: in step S2, after ball milling, the mixture is filtered, washed with 95% ethanol for 3 times, and dried in vacuum at 40°C for 12h.

[0031] As a preferred technical solution of the present invention: in step S3, a graphite mold with an inner diameter of 15 mm is used; the processing temperature is 700-800° C., the applied pressure is 40 MPa; and the insulation time is 10 minutes.

[0032] The second object of the present invention is to provide a nickel-silver-tungsten composite electrical contact material prepared by the preparation method as described above.

[0033] Another object of the present invention is to provide an electrical contact prepared from the nickel-silver-tungsten composite electrical contact material as described above.

[0034] The present invention provides a preparation method of a nickel-silver-tungsten composite electrical contact material, an electrical contact material and an electrical contact. The method of chemical plating is used to introduce silver and nickel metal nanoparticles into the surface of tungsten powder by layered coating to obtain a tungsten powder with a core-shell structure tightly coated with a silver-nickel bimetallic layer; then, different mass fractions of tungsten powder with a core-shell structure are mixed evenly with silver powder by a solution ball milling method; finally, the mixed powder is crystallized and solidified by an electric spark plasma sintering technology to obtain a series of nickel-silver-tungsten composite electrical contact materials. The nickel-silver-tungsten composite electrical contact material provided by the present invention has good compressive strength, excellent ductility and excellent arc erosion resistance; the higher work function of the nickel metal element is utilized to preferentially emit electrons during arc erosion, protecting the tungsten skeleton wrapped inside from being attacked by the arc and generating tungsten oxides under the action of oxygen in the air to reduce the conductivity of the material and increase the temperature rise. In addition, the metal binder effect of the outer layer of nickel metal during the sintering process is utilized to reduce the internal micropores of the nickel-silver-tungsten composite electrical contact material, thereby improving its structural uniformity and mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 Field emission scanning electron microscope photograph of the prepared metal nanoparticle-coated tungsten powder, from top to bottom are W@Ag, W@Ag@Cu and W@Ag@Ni particles.

[0036] Figure 2 XRD spectrum of the prepared bimetallic nanoparticles (W@Ag@Cu and W@Ag@Ni) coated tungsten powder.

[0037] Figure 3 : is the XRD spectrum of the prepared silver-tungsten composite contact material, where: (b) is the enlarged view within the black dotted frame in (a).

[0038] Figure 4 is the Vickers hardness value of the prepared silver-tungsten composite contact material.

[0039] Figure 5 This is the compression test stress-strain curve of the prepared silver-tungsten composite contact material.

[0040] Figure 6 This is a diagram showing the arc erosion resistance of the prepared silver-tungsten composite contact material. DETAILED DESCRIPTION

[0041] A method for preparing a silver-tungsten composite contact material comprises the following steps:

[0042] 1) In an aqueous solution, polyvinyl pyrrolidone, silver nitrate and ammonia water (AR) are dissolved in deionized water respectively, and then the silver ammonia solution is slowly added to the aqueous solution of glucose containing tungsten powder under heating in a water bath while stirring. The reaction lasts for about 30 minutes, and the mixture is allowed to stand for a period of time. After vacuum filtration, washing and vacuum drying, a single-layer silver nanoparticle-coated tungsten powder (W@Ag) is obtained. This is used as a control experiment below and is also the basis for the synthesis of tungsten powder coated with a silver-nickel bimetallic layer.

[0043] 2) In an aqueous solution, 2,2'-bipyridine, dihydrated ethylenediaminetetraacetic acid disodium salt, tetrahydrated potassium sodium tartrate, pentahydrated copper sulfate and flaky sodium hydroxide were added to deionized water respectively, followed by the addition of the product W@Ag powder in step 1, and then slowly added with standard formaldehyde solution under stirring while heating in a water bath, reacted for about 40 minutes, and allowed to stand for a period of time, and vacuum filtered, washed and vacuum dried to obtain a tungsten powder (W@Ag@Cu) double-layer coated with nano-copper and silver particles, which is used as a control experiment below;

[0044] 3) In an aqueous solution, sodium pyrophosphate, nickel sulfate hexahydrate and ammonia water are respectively dissolved in deionized water, and then the product W@Ag powder in step 1 is added, and dimethylaminoborane is added under stirring while heating in a water bath, and the reaction is carried out for about 60 minutes. After standing for a period of time, vacuum filtration, washing and vacuum drying are performed to obtain tungsten powder (W@Ag@Ni) coated with nano-nickel and silver particle layers;

[0045] 4) Weigh the tungsten powder coated with the metal nanoparticle layer prepared by the chemical plating method in the above steps 1, 2, and 3 according to a certain ratio, and add the silver powder to a stainless steel ball mill, add balls and anhydrous ethanol, and then mill. After the milling, let it stand for a period of time, and then vacuum filter, wash, and vacuum dry to obtain a uniformly mixed silver and metal nanoparticle layer coated tungsten powder composite powder;

[0046] 5) Place the uniformly mixed silver and metal nanoparticle layer-coated tungsten powder composite powder obtained in step 4 in a graphite mold, and sinter the powder using spark plasma sintering to obtain a series of silver-tungsten composite contact materials (W@Ag / Ag-MC-ECMs, W@Ag@Cu / Ag-MC-ECMs, W@Ag@Ni / Ag-MC-ECMs).

[0047] In step 1: the amount of deionized water solvent in the silver ammonia solution is 200-400mL, the amount of silver nitrate is 0.85-1.7g, the amount of polyvinyl pyrrolidone is 0.1-0.2g, and the amount of ammonia water is 2-4mL; the mass of tungsten powder added to the glucose solution is 2-10g; the amount of deionized water solvent in the glucose solution is 300-600mL, the amount of glucose is 0.35-0.7g, and the pH value of the solution is between 11-11.5; the specific consumption time of slowly adding the silver ammonia solution is 2-10 minutes; the specific conditions of the reaction are that the water bath temperature is 40°C and the speed of the magnetic stirring is 500rpm; the filter residue is washed with deionized water 3 times in the vacuum filtration step; the vacuum drying temperature is 40°C and the drying is 8h.

[0048] In step 2: the amount of deionized water solvent in the solution is 500-1000mL, the amount of 2,2'-bipyridine is 4-8mg, the amount of ethylenediaminetetraacetic acid disodium dihydrate is 5-11g, the amount of potassium sodium tartrate tetrahydrate is 1-5g, the amount of copper sulfate pentahydrate is 4-8g, the amount of sodium hydroxide is 2-5g, and the pH value of the solution is between 12-13; the mass of W@Ag powder added to the solution is 5-12g; the amount of formaldehyde standard solution is 2-7mL; the specific conditions of the reaction are that the water bath temperature is 40°C and the speed of magnetic stirring is 500rpm; the filter residue is washed with deionized water 3 times in the vacuum filtration step; the vacuum drying temperature is 40°C and the drying time is 8h.

[0049] In step 3: the amount of deionized water solvent in the nickel pyrophosphate ion complex solution is 200-250mL, the amount of sodium pyrophosphate is 10-12.5g, the amount of nickel sulfate hexahydrate is 5-6g, and the amount of ammonia water is 8-10mL; the mass of W@Ag powder added to the nickel pyrophosphate ion complex solution is 10-12g; the amount of dimethylaminoborane is 0.3-0.4g; the specific conditions of the reaction are that the water bath temperature is 25°C and the speed of magnetic stirring is 600rpm; the filter residue is washed 3 times with deionized water in the vacuum filtration step; the vacuum drying temperature is 40°C and the drying is 8h.

[0050] In step 4: the amount of tungsten powder coated with the metal nanoparticle layer is 24-32g, and the amount of silver powder is 3-11g; the powder mass in the ball mill: ball = 1:10, the powder mass: anhydrous ethanol mass = 1:4; the ball mill speed is 250rpm, and the time is 40 minutes; the vacuum filtration step uses 95% ethanol to wash the filter residue 3 times; the vacuum drying temperature is 40°C, and the drying is 8h.

[0051] In step 5: the inner diameter of the graphite mold is 15 mm; the processing temperature is 700-800° C., the applied pressure is 40 MPa; and the holding time is 10 minutes.

[0052] Hereinafter, the present invention will be described in further detail with reference to specific embodiments.

[0053] Example 1

[0054] In an aqueous solution system, 0.1 g (0.2 g / L) of polyvinyl pyrrolidone (K60), 0.85 g (1.7 g / L) of silver nitrate, and 2 mL (4 ml / L) of ammonia water were added to a beaker containing 200 mL of deionized water to prepare a silver ammonia solution. 0.35 g (0.7 g / L) of glucose was added to a round-bottom flask containing 300 mL of deionized water, followed by ultrasonic treatment for 10 minutes, and then the above 200 mL of silver ammonia solution was slowly added at 500 rpm in a 40°C water bath (completed within 5 minutes). After reacting for about 30 minutes, the solution was allowed to stand for a period of time, and then vacuum filtered, washed, and dried to obtain tungsten powder (W@Ag) coated with a nanosilver particle layer.

[0055] The obtained tungsten powder coated with nano-silver particles (W@Ag) was tested by field emission scanning electron microscopy. Figure 1 As shown in a and b, the surface of the tungsten particles is uniformly covered with a layer of spherical silver particles with a size of 20-50nm.

[0056] Example 2

[0057] In an aqueous solution system, 4 mg (8 mg / L) of 2,2'-bipyridine, 5.5 g (11 g / L) of disodium ethylenediaminetetraacetic acid dihydrate, 1.25 g (2.5 g / L) of potassium sodium tartrate tetrahydrate, 4 g (8 g / L) of copper sulfate pentahydrate and 4 g (8 g / L) of flaky sodium hydroxide were added to a beaker containing 500 mL of deionized water in sequence, and 10.5 g of W@Ag powder was ultrasonically treated for 10 minutes, and then 5 mL (10 mL / L) of formaldehyde standard solution was added thereto at 500 rpm in a 40°C water bath. After reacting for 40 minutes, the mixture was allowed to stand for a period of time, and then vacuum filtered, washed and vacuum dried to obtain tungsten powder (W@Ag@Cu) coated with silver and copper nanoparticle layers.

[0058] The obtained tungsten powder coated with silver and copper nanoparticle layers (W@Ag@Cu) was tested by field emission scanning electron microscopy. Figure 1 As shown in c and d, the surface of the W@Ag particles is covered by a layer of tetrahedral scaly copper particles.

[0059] At the same time, the obtained tungsten powder coated with silver and copper nanoparticle layers (W@Ag@Cu) was subjected to XRD test, and the results were as follows Figure 2 As shown, only the characteristic peaks of tungsten, silver and copper are shown, without other impurities.

[0060] Example 3

[0061] In an aqueous solution system, 10 g (50 g / L) of sodium pyrophosphate, 5 g (25 g / L) of nickel sulfate hexahydrate and 8.5 mL (42.5 mL / L) of ammonia water were added to a beaker containing 200 mL of deionized water solution, and then 10.5 g of W@Ag powder was added for ultrasonic treatment for 10 minutes. Then, 0.3 g (1.5 g / L) of dimethylaminoborane was added in a 25°C water bath at 600 rpm. After reacting for 60 minutes, the mixture was allowed to stand for a period of time, and then vacuum filtered, washed and vacuum dried to obtain tungsten powder (W@Ag@Ni) coated with nanosilver and nickel particle layers.

[0062] The obtained tungsten powder coated with silver and nickel nanoparticle layers (W@Ag@Ni) was tested by field emission scanning electron microscopy. The results are as follows Figure 1 As shown in Figures e and f, the surface of the W@Ag particles is covered by a layer of spherical nickel particles.

[0063] At the same time, the obtained tungsten powder coated with silver and nickel nanoparticle layer (W@Ag@Ni) was subjected to XRD test, and the results were as follows Figure 2 As shown, only the characteristic peaks of tungsten, silver and nickel are shown, without other impurities.

[0064] Example 4

[0065] W@Ag@Ni powder and Ag powder were mixed in a solution ball milling process with a silver powder mass percentage of 30wt.%, wherein the W@Ag@Ni and Ag powders were 24.5g and 10.5g, respectively, wherein the mass ratio of powder mass to steel ball was 1:10, and the mass ratio of powder mass to anhydrous ethanol was 1:4. After ball milling at 250rpm for 40 minutes, the mixture was allowed to stand for a period of time, and then filtered, washed, and vacuum dried to obtain a uniformly mixed W@Ag@Ni / Ag composite powder. 30g of the composite powder was poured into a graphite mold with an inner diameter of 15mm, and sintered in a vacuum atmosphere for 10min at a temperature and pressure of 750℃ and 40MPa by electric spark plasma sintering technology, and then cooled to room temperature with the furnace to obtain W@Ag@Ni / Ag-MC-ECMs. Replacing W@Ag@Ni powder with W@Ag or W@Ag@Cu powder can prepare W@Ag / Ag-MC-ECMs and W@Ag@Cu / Ag-MC-ECMs.

[0066] The XRD test results of W@Ag@Ni / Ag-MC-ECMs, W@Ag / Ag-MC-ECMs and W@Ag@Cu / Ag-MC-ECMs are as follows: Figure 3As shown in the figure, only the characteristic peaks of tungsten, silver and nickel exist in W@Ag@Ni / Ag-MC-ECMs, and no other impurities exist. Only the characteristics of W and Ag exist in W@Ag / Ag-MC-ECMs; because the Cu-Ag eutectic phase will dissolve to form a solid solution at 750℃, the characteristic peaks of silver at 38.2°(111) and 44.2°(200) in the XRD spectrum of W@Ag@Cu / Ag-MC-ECMs shift to the high angle direction.

[0067] Example 5

[0068] By changing the mass percentage of the above powders, a series of silver-tungsten composite contact materials can be prepared. The mechanical properties of the silver-tungsten composite contact materials were investigated. The silver-tungsten composite contact materials were cut into 10×10×5mm cuboids by wire cutting, resin embedded at 156°C, polished with 600-mesh, 1000-mesh and 2000-mesh sandpapers in turn, and polished on a polishing machine with diamond polishing paste. The Vickers hardness of the material was tested under a load of 500g for 15 seconds.

[0069] from Figure 4 It can be seen that when the silver content is 30wt.%, the Vickers hardness of W@Ag / Ag-MC-ECMs, W@Ag@Cu / Ag-MC-ECMs and W@Ag@Ni / Ag-MC-ECMs are 160HV, 188HV and 130HV respectively. Compared with W@Ag / Ag-MC-ECMs, W@Ag@Cu / Ag-MC-ECMs has a higher Vickers hardness, and the formation of a uniform Cu-Ag solid solution is the main reason. Because the Cu-Ag solid solution can not only act as an intergranular lubricant to enhance the uniformity of the composite structure, but also produce lattice mismatch, so that the composite material undergoes a hardening transition between grains, inhibiting the dislocation and slip deformation of the composite material. However, W@Ag@Ni / Ag-MC-ECMs did not show the same enhancement effect as W@Ag@Cu / Ag-MC-ECMs. This can be explained by the grain coarsening mechanism, because without effective interfacial bonds and strengthening effects, the introduction of the bimetallic layer increases the particle size of the W@Ag@Ni particles with a dual core-shell structure, reducing the density of the grain boundaries inside the composite material, thereby reducing the hardness strengthening effect of the material.

[0070] The compression test was performed on a Φ5×10mm cylinder at a compression rate of 0.01mm / min using an electronic universal testing machine. Figure 5The results in show that when the silver content is 30wt.%, the compressive strength and fracture deformation rate of W@Ag / Ag-MC-ECMs, W@Ag@Cu / Ag-MC-ECMs and W@Ag@Ni / Ag-MC-ECMs are 303MPa, 590MPa, 598MPa and 8.3%, 23.4%, 22.1%, respectively. For W@Ag@Cu / Ag-MC-ECMs, the solid solution effect shows that the lattice mismatch between the copper solute and the silver matrix leads to lattice deformation; interaction with the surrounding elastic stress field generates stress that hinders dislocation movement and significantly increases the yield stress of the composite. When Ni is uniformly distributed and acts as a metal binder, it improves the interface bonding, reduces the porosity inside the bulk composite, and significantly inhibits the expansion of internal microcracks and micropores caused by load-induced microcracks, which makes the strength and toughness of W@Ag@Ni / Ag-MC-ECMs comprehensively improved.

[0071] Example 6

[0072] The arc erosion resistance of the silver-tungsten composite contact material prepared above was investigated. A rivet-shaped composite silver-tungsten composite contact material was obtained by turning and welded on a copper sheet. Using the JF04D electrical contact test system, an arc erosion resistance experiment was carried out in the air under the AC mode of 250V, 25A, ON 1s, OFF 1s, with copper as the moving contact (anode) and the silver-tungsten composite contact material as the static contact (cathode), with the two contacts 2mm apart.

[0073] from Figure 6The results show that the mass loss of W@Ag@Ni / Ag-MC-ECMs is two orders of magnitude less than that of W@Ag@Cu / Ag-MC-ECMs and W@Ag / Ag-MC-ECMs, and the service life can reach about 1900 times. The mass loss of W@Ag / Ag-MC-ECMs after 833 effective arc erosions is 0.045g; the mass loss of W@Ag@Cu / Ag-MC-ECMs after 1924 effective arc erosions is 0.031g; and the mass loss of W@Ag@Ni / Ag-MC-ECMs after 1883 effective arc erosions is 0.0038g. The reason why W@Ag@Ni / Ag-MC-ECMs has the lowest mass loss and increased effective service life is due to the introduction of metallic nickel. According to the Richardson-Dushman equation, since the work function of Ni (5.15 eV) is higher than that of silver (4.26 eV) and tungsten (4.55 eV), the emission current density will decrease during the arc starting stage, resulting in a decrease in arc energy and reduced arc erosion of the electrical contacts. In addition, during the arc erosion process, in addition to increasing the viscosity of the silver molten pool, the precipitation and dissolution of Ni with a high melting point (1455°C) is also conducive to the dispersion of the arc, making the corrosion surface of W@Ag@Ni / Ag-MC-ECMs relatively flat without large pits, reducing the transfer and splashing of materials from the cathode to the anode.

[0074] At the same time, according to the mass loss characteristics of the cathode and the anode, it can be judged that the arc erosion material transfer direction of the silver-tungsten composite contact material prepared by the present invention is from the cathode to the anode.

[0075] The above-mentioned specific implementation methods are used to explain the present invention and are only preferred embodiments of the present invention, rather than limiting the present invention. Any modifications, equivalent substitutions, improvements, etc. made to the present invention within the spirit of the present invention and the protection scope of the claims shall fall within the protection scope of the present invention.

Claims

1. A method for preparing a nickel-silver-tungsten composite electrical contact material, characterized in that: The method comprises the following steps: S1. Chemical plating under mild conditions in an aqueous solution system: A layer of silver nanoparticles is coated on the surface of the tungsten powder to obtain a tungsten powder coated with a single layer of metallic silver; A layer of nickel nanoparticles is coated on the surface of the obtained single metal silver-coated tungsten powder to obtain a tungsten powder coated with a silver-nickel bimetallic layer; S2, using solution ball milling, mixing the tungsten powder coated with the silver-nickel bimetallic layer with the silver powder using anhydrous ethanol as a dispersant to obtain a composite powder; S3. Using spark plasma sintering, the composite powder is sintered and solidified under high temperature, high pressure and vacuum conditions to obtain a nickel-silver-tungsten composite electrical contact material.

2. The preparation method according to claim 1, characterized in that: Before step S1, the tungsten powder is sensitized by using hydrochloric acid and stannous chloride dihydrate aqueous solution.

3. The preparation method according to claim 1, characterized in that: In step S1, a layer of silver nanoparticles is plated on the surface of tungsten powder using silver nitrate as a silver source, ammonia water as a complexing agent, polyvinyl pyrrolidone as a dispersant, sodium hydroxide aqueous solution as a pH regulator, and glucose as a reducing agent to obtain a tungsten powder coated with a single layer of metallic silver.

4. The preparation method according to claim 3, characterized in that: The amount of silver nitrate is 0.85-1.7g, the amount of ammonia water is 2-4mL, the amount of polyvinyl pyrrolidone is 0.1-0.2g, the amount of glucose is 0.35-0.7g, the mass of tungsten powder is 2-10g, and the pH value of the solution is between 11-11.5; The water bath temperature of the reaction was 40°C and the rotation speed of the magnetic stirrer was 500 rpm.

5. The preparation method according to claim 1, characterized in that: In step S1, a layer of nickel nanoparticles is plated on the surface of the tungsten powder coated with a single layer of metallic silver using nickel sulfate hexahydrate as a nickel source, sodium pyrophosphate as a complexing agent, ammonia water as a pH regulator, and dimethylamine borane as a reducing agent to obtain a tungsten powder coated with a silver-nickel bimetallic layer.

6. The preparation method according to claim 5, characterized in that: The amount of nickel sulfate hexahydrate is 5-6 g, the amount of sodium pyrophosphate is 10-12.5 g, the amount of ammonia water is 8-10 mL, the amount of dimethylamino borane is 0.3-0.4 g, and the mass of the single-layer metallic silver-coated tungsten powder is 10.5-21.0 g; The water bath temperature of the reaction was 25°C and the rotation speed of the magnetic stirrer was 600 rpm.

7. The preparation method according to claim 1, characterized in that: In step S2, The ratio between the total mass of the tungsten powder and the silver powder coated with the silver-nickel bimetallic layer and the mass of the ball milling medium is 1:10; The ratio between the total mass of the tungsten powder and the silver powder coated with the silver-nickel bimetallic layer and the mass of the anhydrous ethanol is 1:4; The ball milling speed was 250 rpm and the time was 40 minutes.

8. The preparation method according to claim 1, characterized in that: In step S3, a graphite mold with an inner diameter of 15 mm is used; the processing temperature is 700-800° C., the applied pressure is 40 MPa; and the insulation time is 10 minutes.

9. A nickel-silver-tungsten composite electrical contact material, characterized in that: The nickel-silver-tungsten composite electrical contact material is prepared by the preparation method described in any one of claims 1-8.

10. An electrical contact, characterized in that: The electrical contact is prepared from the nickel-silver-tungsten composite electrical contact material as claimed in claim 9.

Citation Information

Patent Citations

  • Submicron particle reinforced Ag-based electrical contact material and preparation method thereof

    CN101651050A

  • Processing method for manufacturing silver tungsten composite contact material

    CN102392170A

  • Preparation method of copper-cladded silver-clad tungsten composite clad powder

    CN103464742A

  • Electrical contact material

    JP1984153852A

  • Preparation Method of Electrical Contact Material

    US20160074935A1